(untitled) (Research, Society and Development, 2022)
This study aims to investigate the food consumption of caregivers of elderly people before and after the food workshops. In this sense, a cross-sectional study with 31 participants, whose evaluated population consisted of caregivers from the Health Care Center for the Elderly and their Caregivers (CASIC) of the Fluminense Federal University (UFF), they were submitted to the ELSA questionnaire. A total of N=14 (45.2%) formal caregivers and N=17 (54.8%) informal caregivers were found. In relation to food consumption, a significant reduction in total sugar consumption was found (p-value<0.001), the average energy reduced from 3298.59 Kcal to 1954.40 Kcal, being lower than the recommended average of 2000 Kcal. Mean cholesterol intake also showed a significant reduction (p-value=0.001), with a post-intervention mean close to the recommended ≤ 300mg/day, daily calcium intake showed a reduction (p-value=0.003), sodium and potassium also showed (p-value=0.001). This research showed the lack of food consumption of caregivers of elderly people, which is alarming in the world context, given the increase in life expectancy and the need for comprehensive care for the elderly. Thus, paying attention to the need to formulate adequate nutritional guidelines that address this professional category that is growing widely on a world scale.